2020
DOI: 10.1136/bmjopen-2019-034738
|View full text |Cite
|
Sign up to set email alerts
|

Quality of healthcare for children with severe acute malnutrition in a refugee setting: cross-sectional study in West Nile Region, Uganda

Abstract: Objectives5.0 million annual deaths in low-income and middle-income countries are due to poor quality of care (QOC). We evaluated the QOC provided to malnourished children in West Nile Region in Uganda.DesignCross-sectional study.SettingWest Nile Region, an area hosting over one million refugees.ParticipantsAmong 148 facilities providing nutritional services, 30 randomly selected facilities (20%) and the records of 1467 children with severe acute malnutrition (100% of those attending the 30 facilities during l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…This was also supported by the qualitative study findings in which healthcare providers also admitted that the provision of quality care for the SAM management was not possible due to the lack of support and attention from higher levels of institutions, and lack of supplements, separate unit, laboratory facilities, and training, shortage of staffs. This finding was supported by earlier studies in Northwest Ethiopia, Bangladesh, Iran, Malawi, Ghana, and South Africa ( 3 , 14 , 40 , 46 50 ). However, unlike the findings of the earlier study in Northwest Ethiopia ( 6 ), which reported that urban residents were more likely to perceive the service quality as poor, this study found that urban residents were less likely to rate the service as low quality.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This was also supported by the qualitative study findings in which healthcare providers also admitted that the provision of quality care for the SAM management was not possible due to the lack of support and attention from higher levels of institutions, and lack of supplements, separate unit, laboratory facilities, and training, shortage of staffs. This finding was supported by earlier studies in Northwest Ethiopia, Bangladesh, Iran, Malawi, Ghana, and South Africa ( 3 , 14 , 40 , 46 50 ). However, unlike the findings of the earlier study in Northwest Ethiopia ( 6 ), which reported that urban residents were more likely to perceive the service quality as poor, this study found that urban residents were less likely to rate the service as low quality.…”
Section: Discussionsupporting
confidence: 88%
“…Countries' capacity to provide high-quality care for SAM management is determined by the availability of infrastructure and well-trained staff in public hospitals dedicated to the treatment of malnourished children ( 13 ). Poor quality of care (QOC) has been implicated as a major risk factor for high mortality across conditions, especially in low- and middle-income countries ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…"Global Acute Malnutrition (GAM) prevalence in prevalence in children ranged from 4% to 12% among refugees and 5% to 11% in the hosting population in Uganda [31], and the GAM rate for children in settlement areas in Uganda is high, at 7.3 percent, with some of the highest rates found in the West Nile" [26]. "The burden of malnutrition among refugee children as compared to the children in host communities is high" [31]. Refugees mainly depend on food rations that are insufficient in quantity and variety.…”
Section: Problem Statementmentioning
confidence: 99%